Hours worked long-run trends - Greenwood, Jeremy 1953-; Vandenbroucke, Guillaume (National Bureau of Economic Research, 2005)
"For 200 years the average number of hours worked per worker declined, both in the market placeand at home. Technological progress is the engine of such transformation. Three mechanisms arestressed:(i) The rise in real wages and its corresponding wealth effect;(ii) The enhanced value of time off from work, due to the advent of time-using leisure goods;(iii) The reduced need for housework, due to the introduction of time-saving appliances.These mechanisms are incorporated into a model of household production. The notion of Edgeworth-Pareto complementarity/substitutability is key to the analysis. Numerical examples link theory and data.This note has been prepared for The New Palgrave Dictionary of Economics, 2nd edition, editedby Lawrence E. Blume and Steven N. Durlauf (London: Palgrave Macmillan)"--National Bureau of Economic Research web site.
Keywords: Ökonometrisches Modell; Hours of labor -- Econometric models